Princípio constitucional da proteção integral no trabalho artístico e na prática esportiva infantil - Ferreira, Willian Gonçalves (2018)
This report publishes discloses the importance of comprehensive child protection and part of a diverse hypothesis based on the analysis of children's artistic work and the practice of sport by children and adolescents. While some forms of child labor strike the eyes and cause indignation and perplexity, others run under the eye of admiration and are still encouraged by society. The research covered some labor relations and peculiarities about the worst forms of child labor and the effects of nullities in this field, ending with the prescription. In the following moment, the performance of the child-youth artist in the advertising, entertainment and fashion segment was analyzed. This is one of the most controversial issues among law enforcement and law enforcement agencies that deal with child and adolescent rights advocacy. The research method consisted in the critical revision of the doctrine tangent to the theme, in the primary sources of the labor constitutional law, of the related jurisprudential collection, of the foreign legislation and of the documents published by the International Organizations. The result appears in the media and in society in general. If some are against the authorization of the participation of children and adolescents in this type of activity, arguing that many young artists suffer psychological and social damages in the work environment, others understand that artistic work is a right of the child and the adolescent and that can be exercised in accordance with the principle of integral protection. In compliance with the constitutional norm, there is a public policy to promote youth sports training, through which individuals are stimulated by the State, including through fiscal incentives, to provide adolescent athletes with adequate physical and personal the permanent and competitive practice of sport. Thus, it is necessary to analyze the provisions of the national legislation that regulate sport in its various modalities, as well as the foundations that govern the requirement of the integral protection of the child